Diagnostic yield of TBNA and bronchial biopsy in lung cancer - Kumari, Anita; Gupta, Madhu; Abhesheik, . (International Journal of Research in Medical Sciences, 2017)
Background: Lung cancer has been the most common cancer worldwide since 1985, both in terms of incidence and mortality. In India, approximately 63,000 new lung cancer cases are reported each year. The study was undertaken to detect diagnostic yield of bronchial biopsy and transbronchial needle aspiration in suspected cases of bronchogenic carcinoma. Methods: This was a prospective study including 57 patients having clinical and radiological features of malignancy. Endobronchial forceps biopsy (FB) and transbronchial needle aspiration cytology (TBNA) has been employed during fiber-optic bronchoscopy. The statistical analysis was done using chi-square test. Results: Out of total 57 patients, 43 were found malignant on FB plus TBNA. The majority of patients (59.45%) were found to have squamous cell carcinoma on biopsy followed by Adenocarcinoma (16.21%), Small cell carcinoma (13.51%) and untypable cases (10.81%). On TBNA majority of patients (41.93%) could not be typed into any of the specific subtype. Out of rest typable carcinoma majority were squamous cell carcinoma (35.48%). Sensitivity of TBNA in diagnosing lung malignancy was 67.6%. The yield of TBNA, FB and TBNA plus FB was 54.38%, 64.91% and 75.43% respectively. Additional yield of TBNA over FB was 10.52%. Conclusions: TBNA is a beneficial, safe and minimally invasive bronchoscopic technique and may be considered routinely during Fiberoptic Bronchoscopy procedure to increase the yield with insignificant side effects in the diagnosis of bronchogenic carcinoma.